Estudio de la disponibilidad y calidad del agua de consumo humano a través del monitoreo de caudales y análisis de los parámetros físicos, químicos y microbiológicos en la zona Pesillo - Imbabura - Chamba Moreno, Karina Lizeth (2015)
This research project "Study the availability and quality of water for human consumption Through Flow Monitoring Of Analysis And Physical, Chemical and microbiological Parameters in Pesillo–Imbabura zone" aims to analyze the quality, quantity and availability of water for human consumption through flow monitoring, physicochemical and microbiological analyzes of ten Regional Water Boards belonging to the Council of Community Boards Drinking Water Pesillo - Imbabura, in order to generate information Community boards and obtain a water quality management for efficient and healthy human consumption. The study comes from the formulation of projects through the Center for Research in Environmental Modeling (CIMA) and the Department of Collective Engagement, belonging to the Salesian Polytechnic University to study and suggest alternative solutions to the problems arising in the social environment in rural areas and the social management of drinking water Pesillo-Imbabura. The location of the study is north of the Ecuadorian territory in the central Andean region comprises two provinces, the province of Imbabura, in Ibarra, Otavalo cantons and Antonio Ante; and the province of Pichincha in the Pedro Moncayo canton. The experimental design chosen for determining the quality and availability of water for human consumption consisted of two phases: technique phase is the work done in the field and the analysis phase made in desk. Some technical phase was the completion of two phases flow monitoring and water sampling of the different units of community water systems, according to two climatic seasons characteristics of the study area, the summer season (March and April) and winter season (September and October). The availability of water for human consumption is determined by the choice and application of the volumetric method while determining water quality single sampling was performed with making a single water sample taken for microbiological and chemical physical analysis to Lab of Soil and Water Samples Analysis Polytechnic University Salesian headquarters at Cayambe.. Data generation was obtained by in situ application of technical specifications, which contributed to the tabulation of flow measurement and interpretation of chemical and microbiological water physical parameters. The results were obtained by managing database and conducting Excel PivotTables to determine the availability of water in the ten Regional Water Boards. The determination of water quality was performed by comparing the data obtained in laboratory tests with the parameters specified in the Ecuadorian Technical Norma INEN 1108 - "Specific requirements for drinking water," generating a percentage of compliance with interpreting it as the norm and quality.